"In America?": Children, Violence, and Commodification in Stephen King's The Institute. Issue 2 (1st June 2021) - Mercer, Erin
Abstract : Critical evaluation of Stephen King's work is far from unanimous, with a handful of scholars producing monographs devoted to his fiction, while others dismiss him as a peddler of poorly written popular narratives motivated only by commercial success. King himself acknowledges that he is as much a brand name as an author, and that he might be considered "the literary equivalent of a Big Mac and a large fries from McDonalds." Anxieties related to the aesthetic value of prolifically produced popular fiction appear to be validated by King's novel, The Institute (2019), which treads the familiar terrain of the King brand by utilizing the genre of speculative fiction and focusing on a child with paranormal powers. Nevertheless, although The Institute repeats many of King's abiding concerns and tropes, it represents a significant development in his work. Less a reiteration of King's earlier speculative fiction depicting children with telekinetic, telepathic, and pyrokinetic powers, The Institute demonstrates significant complexity and nuance in its representation of power, good and evil, and the ethics underpinning American life in the twenty-first century. In addition to critiquing corrupt social structures, The Institute interrogates the assumed powerlessness of children and condemns the commodification of the human subject by late capitalist society and its militarized forms of order. In his novel, King proves his detractors wrong by not simply reproducing his particular brand of fiction but revising its previous representations in order to meaningfully engage with a rapidly changing world.